Carbamazepine degradation through peroxymonosulfate activation by α-MnO2 with the different exposed facets: Enhanced radical oxidation by facet-dependent surface effect. Issue 5 (October 2022) - Wei, Haoxuan; Zhao, Jujiao; Shang, Bo; Zhai, Jun
Abstract: Removing carbamazepine (CBZ) from wastewater through peroxymonosulfate (PMS) activation with low-toxic and earth-abundant heterogeneous catalysts is highly desired. In this study, three facet engineered α-MnO2 were prepared for activating PMS towards CBZ degradation. The 310-α-MnO2 /PMS system removes 100% of CBZ in 30 min with the kinetics constant per surface area of 0.0803 min −1 ∙m −2, which is 4.12 and 1.65 times higher than those of 110-α-MnO2 and 100-α-MnO2, respectively. Sulfate radicals (SO4 ∙- ), hydroxyl radicals, and singlet oxygen were detected in 310-α-MnO2 /PMS system, and SO4 ∙- made the major contribution to CBZ degradation. Interestingly, the CBZ degradation performances of 310-α-MnO2, 110-α-MnO2, and 100-α-MnO2 are not linear correlated with Mn(III) content, electron transfer capacity, and PMS adsorption energy, all of which are commonly regarded as key factors towards PMS activation. Based on both experimental results and density functional theory (DFT) calculation, it is suggested that despite the adsorption amount of CBZ on α-MnO2 is negligible, the facet-dependent surface effect still plays an important role on SO4 ∙- dominant CBZ degradation, which could be attributed to the stretched bond length of the adsorbed CBZ. This study would provide an effective method for CBZ degradation, and guide the development of heterogeneous catalysts/PMS system for organic pollutants degradation. Graphical Abstract: ga1 Highlights: The kinetics constant per surface area of the 310-α-MnO2 achieves 0.0803 min −1 ∙m −2 . (310) facets exhibit the best reactivity compared to (100) and (110) facets. SO4 ∙- plays a dominant role in the degradation of CBZ in α-MnO2 /PMS system. The facet-dependent process plays an important role in CBZ degradation.